A Jurisprudence Study of the Purposes (Maqasid) of Sharia for Preserving Social Relations by the Quranic Verse of Acquaintance - عبد الملك عبد الله أحمد الزبيري (مجلة الدراسات الاجتماعية, 2018)
The claim of some Muslim communities for racial selection and racial discrimination, knowingly or unknowingly, and their ignorance of the goals of equality and the preservation of human dignity has caused the emergence of some social diseases that plagued the Islamic communities. This also has led to the spread of division, selfishness and hatred. Therefore, this study aimed to investigate equality and the preservation of human dignity in the Quranic verse of acquaintance to show how Allah Almighty stressed these two purposes (Maqasid), their importance and the need to comply with them, in order to ensure equality and justice, and to achieve the rest of other purposes related to the preservation of the five necessities. The researcher used the inductive, descriptive and analytical approach. The research concludes that the origin of mankind is Adam and Eve (Peace Be Upon Them) and that the application of the purposes of equality and the preservation of human dignity is a guarantee for brotherhood and other purposes. This is the only way to eliminate the social diseases that resulted from ignorance of these two purposes. The non-application of these two purposes will make the Muslim nation lose great benefits, and will cause many evils.